1925
DOI: 10.1002/cber.19250580418
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis des Fluorocyclens

Abstract: steht. Wir haben bereits eine Anzahl anderer Halogenverbindungen untersucht, ohne bisher einen gleichartigen Reaktionsverlauf verwirklichen zu kijnnen. Die Reaktion hangt also wohl im wesentlichen von der Konstitution der Halogenverbindung ab. Wir beabsichtigen daher, diese Untersuchung einerseits auf weitere Halogenverbindungen, insbesondere Acetohalogenzucker, auszudehnen, andererseits den Einfld des Lasungsmittels zu studieren und schliel3lich andere Sake des Silbers, wie auch solche mit anderen Kationen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1930
1930
1951
1951

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the study of the polymerization of acenaphthene at high temperatures (45), a very high-melting crystalline compound, CísHís, was obtained in 4-5 per cent yield. The material, fluorocyclene, was considered to have one of the two following structures: Subsequent work (44,46,47) showed that fluorocyclene can be produced in yields of 25-38 per cent when the acenaphthene is heated at high temperatures in the presence of lead oxides.…”
Section: F By Miscellaneous Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of the polymerization of acenaphthene at high temperatures (45), a very high-melting crystalline compound, CísHís, was obtained in 4-5 per cent yield. The material, fluorocyclene, was considered to have one of the two following structures: Subsequent work (44,46,47) showed that fluorocyclene can be produced in yields of 25-38 per cent when the acenaphthene is heated at high temperatures in the presence of lead oxides.…”
Section: F By Miscellaneous Methodsmentioning
confidence: 99%
“…Fluorocyclene adds bromine to give a dibromo and a tetrabromo derivative and can be nitrated to give dinitro and tetranitro compounds and sulfonated to give a tetrasulfonic acid (47). With sodium and alcohol, tetrahydro, octahydro, and dodecahydro derivatives are produced (44).…”
Section: G Miscellaneous Eight-membered Carbocyclesmentioning
confidence: 99%